A critical role of farnesol in the modulation of Amphotericin B and Aureobasidin A antifungal drug susceptibility. Issue 4 (2nd October 2022) - Mahendrarajan, Venkatramanan; Bari, Vinay Kumar
ABSTRACT: Candida albicans and its related species can cause opportunistic infections such as "candidiasis" in immunocompromised individuals with a high morbidity and mortality rate. Several antifungal drugs available in the market are often used to treat infections caused by pathogenic fungi. However, in fungi, the development of resistance against these drugs quickly evolved. Candida is a dimorphic fungus that can switch between yeast to hyphae form, requires an active biosynthesis of membrane constituents. Sphingolipid and ergosterol molecules, are the major fungal plasma membrane components, and their interaction with the antifungal drug can modulate drug susceptibility. A lipophilic compound farnesol acts as a quorum-sensing molecule synthesised by the isoprenoid biosynthesis pathway in the fungal pathogen Candida . Farnesol is secreted in a cell density-dependent manner inhibits hyphae germination and biofilm formation. In this study, we have investigated whether the farnesol molecules affect the drug susceptibility of the antifungal drug Amphotericin B (AmB) which mainly binds with ergosterol, and Aureobasidin A (AbA), a complex sphingolipid biosynthesis inhibitor. Our studies revealed that a non-toxic and low concentration of farnesol can reduce the efficacy of AmB and AbA on yeast cells. This reduction is probably through the alteration in the complex sphingolipid biosynthesis and ATP-binding cassette (ABC) type membrane transport activity. These findings may shed light on a new direction to explore the role of lipid molecules in the antifungal drug resistance mechanisms in pathogenic yeast.